2013
DOI: 10.1021/ac303174n
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength-Resolved Optical Extinction Measurements of Aerosols Using Broad-Band Cavity-Enhanced Absorption Spectroscopy over the Spectral Range of 445–480 nm

Abstract: Despite the significant progress in the measurements of aerosol extinction and absorption using spectroscopy approaches such as cavity ring-down spectroscopy (CRDS) and photoacoustic spectroscopy (PAS), the widely used single-wavelength instruments may suffer from the interferences of gases absorption present in the real environment. A second instrument for simultaneous measurement of absorbing gases is required to characterize the effect of light extinction resulted from gases absorption. We present in this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 44 publications
1
55
0
Order By: Relevance
“…Engineering improvements since the NO3Comp campaign, including more frequent re-calibration of the baseline spectrum, have produced performances much closer to the best case values (Kennedy et al, 2011). Zhao et al (2013) report a long-term stability of around 1 Mm −1 , which is only slightly worse than the detection limit of their instrument. The detection limits we report are well sufficient for monitoring aerosol extinction in polluted atmospheres (for instance, mean aerosol extinction coefficients are 121 Mm −1 in Atlanta, and over 300 Mm −1 in Beijing) and are possibly low enough for measurements in pristine environments (Carrico et al, 2003;He et al, 2009).…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Engineering improvements since the NO3Comp campaign, including more frequent re-calibration of the baseline spectrum, have produced performances much closer to the best case values (Kennedy et al, 2011). Zhao et al (2013) report a long-term stability of around 1 Mm −1 , which is only slightly worse than the detection limit of their instrument. The detection limits we report are well sufficient for monitoring aerosol extinction in polluted atmospheres (for instance, mean aerosol extinction coefficients are 121 Mm −1 in Atlanta, and over 300 Mm −1 in Beijing) and are possibly low enough for measurements in pristine environments (Carrico et al, 2003;He et al, 2009).…”
Section: Discussionmentioning
confidence: 75%
“…Based solely on the precision of the extinction coefficient measurements, the respective limits of detection (3σ ) of the three systems were respectively 1.2, 2.1, and 1.2 Mm −1 for the BBCRDS and CE-DOAS systems over 60 s, and for the IBBCEAS system over 5 s. Other recently developed broadband systems by Washenfelder et al (2013) and Zhao et al (2013) have reported somewhat lower precisions of around 0.2 Mm −1 (corresponding to a detection limit of 0.6 Mm −1 ). These figures represent the best case performance of the instruments and do not take into account any drift in the instruments' baselines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ensemble broadband cavity-enhanced spectroscopy involves σ ext measurements on a cloud of aerosol particles over a broad range of wavelengths. Zhao et al (2013) have developed an ensemble broadband cavity-enhanced spectrometer for measurements of σ ext over the wavelength range 445-480 nm and reported measurements of (NH 4 ) 2 SO 4 aerosol (Zhao et al, 2013). Rudich and co-workers developed an ensemble broadband cavity-enhanced spectrometer for the wavelength range 360-420 nm (Flores et al, 2014a, b;Washenfelder et al, 2013).…”
Section: Introductionmentioning
confidence: 99%